2008
DOI: 10.1111/j.1365-2249.2008.03598.x
|View full text |Cite
|
Sign up to set email alerts
|

Soluble human leucocyte antigen-G molecules in peripheral blood haematopoietic stem cell transplantation: a specific role to prevent acute graft-versus-host disease and a link with regulatory T cells

Abstract: Haematopoietic stem cell transplantation is often complicated by the life-threatening graft-versus-host disease (GVHD) which consists of an allogeneic reaction of the graft cells against the host organs. The aim of this study was to investigate the putative involvement of soluble human leucocyte antigen (sHLA) class I molecules, and particularly sHLA-G molecules, in the occurrence and/or prevention of acute GVHD (aGVHD) in allogeneic peripheral blood stem cell (PSC) transplantation. Whole sHLA class I molecule… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
27
2

Year Published

2010
2010
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(33 citation statements)
references
References 38 publications
4
27
2
Order By: Relevance
“…48,49 They are also in agreement with those showing that high HLA-G5 plasma levels in the peripheral blood of stem cell-transplanted patients are associated with the expansion in peripheral blood of CD4 ϩ CD25 ϩ CD152 ϩ T cells with suppressive activity. 50 Soluble HLA-G up-regulated the expression of ILT2, ILT3, and ILT4 by lymphocytes and myeloid cell lines. 51 It is BLOOD, 15 DECEMBER 2011 ⅐ VOLUME 118, NUMBER 25 For personal use only.…”
Section: Hla-g and Regulatory Cellsmentioning
confidence: 99%
“…48,49 They are also in agreement with those showing that high HLA-G5 plasma levels in the peripheral blood of stem cell-transplanted patients are associated with the expansion in peripheral blood of CD4 ϩ CD25 ϩ CD152 ϩ T cells with suppressive activity. 50 Soluble HLA-G up-regulated the expression of ILT2, ILT3, and ILT4 by lymphocytes and myeloid cell lines. 51 It is BLOOD, 15 DECEMBER 2011 ⅐ VOLUME 118, NUMBER 25 For personal use only.…”
Section: Hla-g and Regulatory Cellsmentioning
confidence: 99%
“…The insertion of 14 bp is associated with a decreased mRNA stability and a consequent lower HLA-G protein expression. 4,13,14 Moreover, this polymorphism has a pharmacogenetic role in MTX treatment. Recent data have demonstrated that MTX induces higher HLA-G production in subjects homozygous for the 14 bp del allele influencing the response to the therapy.…”
Section: Discussionmentioning
confidence: 99%
“…2 HLA-G antigens function as immunomodulatory molecules inhibiting natural killer cell activity, CD4 þ T lymphocyte and DC maturation, inducing apoptosis in activated CD8 þ CTLs and the development of regulatory T cells. 3,4 In physiological conditions, HLA-G molecules are expressed by peripheral blood CD14 þ monocytes and thymic epithelial cells. HLA-G antigens have been detected in pathological conditions such as in autoimmune and inflammatory diseases, viral infections, 5,6 tumours 7,8 and in transplantation.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, there are data suggesting that an alloreaction itself might up-regulate the HLA-G expression. 36 In the only study analyzing the role of HLA-G in the allo-HCT setting, Le Maux et al 15 found increased soluble HLA-G plasma levels in patients without acute GvHD as compared to those patients with, and suggested a preventative role of this molecule in the occurrence of acute GvHD. In our study, we did not find any correlation between the frequency of the HLA-G pos cells and active GvHD, history of acute or chronic GvHD, severity of chronic GvHD or treatment with immunosuppressive drugs.…”
Section: Discussionmentioning
confidence: 99%
“…After allogeneic bone marrow transplantation, soluble HLA-G plasma levels have been suggested to correlate with the occurrence of acute graft-versus-host disease (GvHD), suggesting an involvement of HLA-G in GvHD prevention. 15 Unlike the highly polymorphic classic HLA class I molecules, HLA-G is expressed as only seven protein isoforms (HLA-G1 to -G4 membrane-bound and soluble HLA-G5 to -G7) that are generated by alternative splicing. 3 In vitro functional studies with membrane-bound HLA-G 16 or soluble HLA-G5 17 expressing cell lines have recognized the HLA-G molecule as an important mediator of immune tolerance, as it may: i) inhibit natural killer and T-cell cytotoxicity; ii) induce apoptosis in activated CD8 + T cells; iii) suppress alloreactive CD4 + T-cell proliferation; iv) generate suppressor T cells; and v) impair antigen-presenting cell function.…”
Section: Introductionmentioning
confidence: 99%